Socioeconomic analysis of deforestation and economically sustainable farming systems to foster forest landscape restoration in central Togo - Moluh Njoya, Hamza; Hounkpati, Kossi; Adjonou, Kossi; Kokou, Kouami; Sieber, Stefan; Löhr, Katharina (Frontiers in Sustainable Food Systems, 2024)
Cropland expansion, driven by increasing population pressure and economic demands, is a major contributor to accelerating deforestation. While most studies have focused on the spatial and temporal analysis of landscape changes using Geographic Information Systems (GIS) and remote sensing, there has been less emphasis on the socioeconomic analysis of these changes. Understanding the socioeconomic dynamics of affected areas is essential for implementing practical corrective actions. We apply linear programming and welfare maximization theory to examine how population growth impacts competition between agriculture and forest land use, per capita cash income, and subsistence consumption from privately owned farms. Focusing on the Tchamba district in Togo, we aim to determine the sustainability of farming systems to better inform the ongoing Forest Landscape Restoration (FLR) program. The findings show that the current agricultural systems can support the population growth rate (2.68% per year in the Tchamba district) and per capita income until at least 2063. However, the current agricultural systems cannot support one human generation, which is estimated to be 65 years. These results underscore the need to enhance farming technologies, boost land productivity, diversify income sources to meet the rising food demand and curb forest clearing for farmland expansion. By integrating these insights into the FLR program, this research highlights the importance of a comprehensive policy framework that supports sustainable agricultural practices, community engagement, enforcement of regulations, and economic diversification. This approach will guide restoration efforts and strengthen the resilience and productivity of agricultural systems under population and income pressures.